Answer:
I don't think so.
Step-by-step explanation:
1/2p-(1/4p-4)
1/2p-(1-16p/4p)
(2p-1+16p)/4p
(18p-1)/4p
2(9p-1)/4p
9p-1/2p
Answer:
400
Step-by-step explanation:
just took the test lol
That would be :
4x – 10 = x2 – 5x + 10 ( y = 4x - 10 is substitute for y)
PROOF: y + 5x = x²<span> + 10
</span> (4x - 10) + 5x = x² + 10
4x - 10 = x² -5x + 10
<span>
</span>0 = x2 – 9x + 20<span> (liked terms are grouped and simplified)
PROOF: </span> 4x - 10 = x² -5x + 10
4x = x² -5x + 10 + 10
0 = x² -5x -4x + 20
0 = x² - 9x + 20
Solving:
x² - 9x + 20 = 0
x² - 5x - 4x + 20 = 0
(x - 5) (x - 4) = 0
⇒ x = 4 (as question says) OR x = 5